Short implants to support mandibular complete dentures - photoelastic analysis - Marcele Jardim PIMENTEL; Wander José da SILVA; Altair Antoninha DEL BEL CURY (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract This study evaluated the stress behavior around short implants in edentulous atrophic mandibles. Six groups included implants with two diameters regular and wide (4 and 5 mm) and three lengths (5, 7 and 9 mm) as follows: Ci9 (9 x 4 mm), Ci7 (7 x 4 mm), Ci5 (5 x 4 mm), Wi9 (9 x 5 mm), Wi7 (7 x 5 mm) and Wi5 (5 x 5 mm). These groups were compared to the control group CG (11 x 4 mm). The analysis was performed with the photoelastic method (n = 6). Each model comprised 4 implants with the same length and diameter connected by a chromium-cobalt bar that simulates a fixed denture. A 0.15 kg force was applied at the end of the cantilever (15 mm), and the maximum shear stress was recorded around the distal and subsequent implants. The stress values were determined, and the quantitative data (Fringes®) were submitted to statistical analysis with one-way ANOVA and the Dunnett test (p < 0.05). It was observed that the reduction in implant length increased stress values with a significant difference (p < 0.05) between CG Ci7 and Ci5, while the increase in implant diameter reduced the stress values without any differences found between short and long implants. Implants with 5 and 7 mm with regular diameter increased stress levels while short implants with larger diameters experienced similar stress to that of longer implants.